Spiritual origin of national patriotic education in the military chaplaincy system - Ірина Ломачинська; Олена Алексеєнко (Cхід, 2024)
The article examines the role of military chaplaincy in the formation of national-patriotic education of the Ukrainian army. The relevance and novelty of the research lies in determining the essence of Ukrainian military patriotism’s spiritual foundations, which is formed on the archetypes of "clan", "Father", "Mother", "Family". Historically, "Father" embodies power, dominion not only over the body, but also over the soul, he brings conscience and moral grounds for subordination in the entire military family, based on the principles of fraternity. The archetype of "Mother" was formed from ancient Slavic ideas about Berehynia, in the Christian era it receives a new incarnation in the image of the Mother of God as the heavenly protector of the entire human race.